Analisis Hukum: Actio Pauliana terhadap Aset Disewakan dalam Kepailitan - Sunur, Fransiskus Stefan; Anakotta, Marthsian Yeksi (Universitas Batanghari Jambi, 2024)
This research focuses on the legal regulation of leasing in the context of bankruptcy, emphasizing the importance of good faith principles and the application of actio pauliana. Leasing involves managing economically valuable assets through agreements that must comply with the validity requirements under Article 1320 of the Indonesian Civil Code, including the principle of good faith. In bankruptcy cases, the good faith principle is applied through actio pauliana, which grants creditors the right to annul actions by debtors that harm them. This research aims to understand how the Bankruptcy and Suspension of Debt Payment Obligations Law (KPKPU) regulates rental income from bankruptcy assets and the application of actio pauliana to leased bankruptcy assets. The study employs a normative juridical method with legislative and conceptual approaches to analyze the legal certainty of leased bankruptcy assets. The findings show that rental income can be classified as bankruptcy assets under Article 38 of the KPKPU Law, and actio pauliana can be applied if the leasing agreement is made in bad faith, as per Article 1341(2) of the Civil Code and Article 38 of the KPKPU Law.